Acute onset low back pain leading to a diagnosis of cauda equina syndrome: a case study. (2nd February 2022) - Read, Haley; Mortimore, Gerri
Abstract : Cauda equina syndrome is rarely seen in primary care, but advanced practitioners must be aware of the possibility. Haley Read and Gerri Mortimore highlight a case study leading to a diagnosis of the condition One of the most common symptoms managed in primary care is lower back pain, which affects approximately 20% of the UK population at any one time (National Collaborating Centre for Primary Care, 2009 ). There are many differential diagnoses for the cause of back pain, with one such potential diagnosis being cauda equina syndrome. In this instance, it is of paramount importance that the correct diagnosis is reached quickly with urgent referral into secondary care for the instigation of treatment to prevent paralysis. This case review will examine a patient presenting to primary care with lower back pain and diagnosed with cauda equina syndrome.